Morphological characteristics of the soils under different land uses in Universiti Putra Malaysia, Selangor - Abdul Malik, Mohammad Nazrin; Abdu, Arifin; Karam Singh, Daljit Singh; Jusop, Shamshuddin; Karim, Md. Rezaul; Abdul Hamid, Hazandy; Jamaluddin, Aiza Shaliha; Rajoo, K. S.; Patek Mohd, Nur Nazirah (Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2015)
Assessing land use-induced changes in soil properties are essential for addressing issues of agro-ecosystem transformation and sustainable land productivity. Soil profiles were dug and samples were collected according to genetic horizons to assess the impact of land use/land cover of five land use types, namely Pinus caribaea plantation (PP), Swietennia macrophylla plantation (MP), pasture area (PA), oil palm plantation (OP) and secondary forest (SF), Universiti Putra Malaysia Serdang Selangor, Malaysia. A horizon was found in all the soil profiles. Therefore, it could be concluded that results from these sites were influenced by the weathering of the parent materials, human activities, and vegetation.